Driving sustainability transitions through financial tipping points - N. Ameli; H. Chenet; H. Chenet; M. Falkenberg; M. Falkenberg; S. Kothari; J. Rickman; F. Lamperti; F. Lamperti (Earth System Dynamics)
Achieving a net-zero-carbon economy requires significant structural changes in the financial system, driving a substantial shift in investment towards low-carbon assets. This transformation of finance is necessary beyond the aim of climate stabilization but is more broadly required to foster sustainably thriving economies. In this paper, we offer a critical discussion of the positive tipping points that can be activated in the financial system to accelerate a fast, sustainable transition. Identifying and leveraging these critical and positive tipping points can amplify sustainable investments and foster transformative changes in the practices of the financial sector. By aligning expectations, steering herding behaviour, mobilizing public finance, reducing capital costs, reaching low-carbon investment thresholds in developing nations, and enforcing robust financial regulations and policies, the financial system can assume a central role in re-orienting economies onto a net-zero and sustainable course. Taken together, such mechanisms highlight the positive tipping points that can be triggered within sustainable finance and emphasize the necessity of policy interventions to activate and capitalize on these dynamics.